A Model for Determining Students’ and Teachers’ Perspectives on the Turkish 11th Grade English Language Curriculum in Terms of Achieved Learning Outcomes - Gürbüz Ocak; Burcu Karafil (Journal of Educational Issues, 2024)
In the current study, it was aimed to evaluate the Turkish 11th grade English language curricula implemented in Turkey in terms of achieved learning outcomes. In the study, case study model was employed. The data were obtained from 20 11th grade high school students and an English language teacher in the spring term of 2018-2019 academic year. “Learning Outcomes Questionnaire for Students” was prepared by the researchers in order to obtain data from the students to determine their self-efficacy perceptions about achieving the Turkish 11th grade English curriculum learning outcomes. The second data collection tool was “Learning Outcomes Questionnaire for Teachers”. This questionnaire was also prepared by the researchers for the teachers to determine teachers’ opinions about the degree that students achieved the learning outcomes. Open-ended questions were prepared and asked to the teacher to obtain the qualitative data Moreover, classroom observations were carried out during four weeks, and one class hour of observation was made per week. The findings of the study showed that the students’ self-efficacy perception on “Pronunciation” skill was at highest level ( = 3.68) while their perception on “Reading” skill was at lowest ( = 2.94). Similarly, the teacher’s mean score was at highest level for “Pronunciation” skill while it was lowest for “Reading” skill.